2019
DOI: 10.1016/j.fochx.2019.100037
|View full text |Cite
|
Sign up to set email alerts
|

Formation of phenylacetic acid and benzaldehyde by degradation of phenylalanine in the presence of lipid hydroperoxides: New routes in the amino acid degradation pathways initiated by lipid oxidation products

Abstract: Highlights Degradation of phenylalanine into phenylacetic acid and benzaldehyde is described. Amino acid degradation by lipid hydroperoxides takes place in two steps. First step: phenylpyruvic acid and phenylacetaldehyde are formed by lipid carbonyls. Second step: phenylpyruvic acid and phenylacetaldehyde are broken by lipid radicals. Concerted action of both carbonyl-amine and free radical reactions is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…The origin of lower aliphatic carbonyl compounds during drying may be related to pronounced oxidation and decomposition reactions of lipid-derived compounds, as was noted in our other research on the algae [ 15 ]. On the other hand, the appearance of benzaldehyde during drying under conditions of lipid oxidation and air access can be connected with a recent model study [ 16 ]. The study showed that benzaldehyde and phenylacetic acid can occur by the chemical routes of lipid oxidation [ 16 ].…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The origin of lower aliphatic carbonyl compounds during drying may be related to pronounced oxidation and decomposition reactions of lipid-derived compounds, as was noted in our other research on the algae [ 15 ]. On the other hand, the appearance of benzaldehyde during drying under conditions of lipid oxidation and air access can be connected with a recent model study [ 16 ]. The study showed that benzaldehyde and phenylacetic acid can occur by the chemical routes of lipid oxidation [ 16 ].…”
Section: Resultsmentioning
confidence: 79%
“…On the other hand, the appearance of benzaldehyde during drying under conditions of lipid oxidation and air access can be connected with a recent model study [ 16 ]. The study showed that benzaldehyde and phenylacetic acid can occur by the chemical routes of lipid oxidation [ 16 ]. Their occurrence is complex and involves carbonyl-amine reactions (or Maillard reactions) in the first stage to produce phenylacetaldehyde, phenylpyruvic acid, or β-phenylethylamine, which were further degraded by the free radicals from the lipid hydroperoxides decomposition to form benzaldehyde and phenylacetic acid.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Other authors also reported an increase in V10 with the roasting conditions (time and temperature) in roasted sunflower seeds. This phenomenon might occur as a consequence of lipid oxidation in which a carbonyl‐amine reaction (Strecker degradation) is required to produce compounds that would be later degraded by the free radicals produced in the decomposition of lipid hydroperoxides to benzaldehyde and other compounds (Hidalgo & Zamora, 2019). In addition, “Vario” cultivar is characterized by very low levels of benzaldehyde in raw almonds (Lipan et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, reactive carbonyls in foods are not only produced from carbohydrates. Other major food components also produce carbonyl compounds and, therefore, contribute to flavor generation by carbonyl-amine reactions (Hidalgo & Zamora, 2019). Thus, for example, lipid-derived reactive carbonyls have been shown to convert amino acids into Strecker aldehydes, -oxoacids, and amine compounds, among other flavor-contributing substances , and quinones have been shown to promote Strecker degradation of amino acids (Delgado, Zamora, & Hidalgo, 2015).…”
Section: Introductionmentioning
confidence: 99%